1049 The Emergence of Cheyne-Stokes-Breathing in a Patient with Atrial Fibrillation and an Implanted Hypoglossal Nerve Stimulator. (12th April 2019) - Hong, Hanna; Oster, Joel; Grover, Aarti; Schumaker, Greg; Wein, Richard; Ismail, Khalid
Abstract: Introduction: Atrial fibrillation (AF) is a common arrhythmia associated with idiopathic central sleep apnea (CSA), even without congestive heart failure. CSA may predict subsequent AF. 1 Treatment emergent central sleep apnea (TECSA) can occur with positive airway pressure (PAP) therapy for obstructive sleep apnea (OSA), and there have been recent cases denoting TECSA after treatment with the hypoglossal nerve stimulator (HNS). We present a difficult case of a patient with chronic AF and propensity for TECSA found to have Cheyne Stokes Breathing (CSB) after use of the HNS therapy for OSA. Report of Case: A 76 year-old male with chronic AF and severe OSA used PAP successfully for 10+ years until two pneumothoraces occurred. Mandibular advancement device and nasal expiratory positive airway pressure were attempted, and he was referred for the HNS device. Diagnostic polysomnography prior to implantation indicated a central apnea index (CAI) of 0.7/hour, and an apnea-hypopnea index (AHI) of 18.6/hour. After HNS implantation, a titration polysomnography study two months after activation denoted CSB. Echocardiography showed no evidence of heart failure and there was normal brain imaging. To distinguish TECSA versus primary CSA, a "wash-out period" during which the HNS device was not used for two weeks occurred and he had a repeat diagnostic polysomnogram which denoted an obstructive AHI of 26.7/hour and a CAI of 37.8/hour. Retrospectively, previous polysomnography done with therapy for OSA had consistently elevated CAIs. We speculate that due to the AF in combination with high loop gain activated by treatment for OSA, he developed worsening symptomatic CSA in a perpetuating cycle. We recommended continuing his HNS device for OSA treatment. To treat his CSA he was prescribed acetazolamide and eszopiclone with referral to electrophysiology to consider benefit from restoration into sinus rhythm. Conclusion: CSA >25% of the total AHI is a contraindication for implantation of the HNS to treat OSA. Care must be taken to closely monitor patients with chronic AF as patients may develop worsening CSA especially those with a propensity for high loop gain. Further research is needed on CSA in patients with HNS implantation and AF.